Design of a Sequential Axial Turbocharger for Automotive Application - Constantinos Panayides (Energies, 2019)
In the last few years, the perspective of climate change, energy, competitiveness, and fuel consumption in the transportation sector has become one of the most significant public policy issues of our time. As different methods are being adapted into light-duty vehicles like engine downsizing, on the other hand, the increase in carbon emissions of heavy-duty trucks is becoming a major concern. Although previous researches have studied the methodology for selecting optimized turbocharger performance, still further investigation is needed to create a method for achieving the highest performance for a sequential axial turbocharger. Therefore, in this study, the design of a two-stage turbocharger system that consists of a radial turbine connected in series to an axial turbine is considered. The specific two-stage turbine was designed specifically and will be tested on a MAN 6.9 L diesel truck engine. With the engine already equipped with a radial type turbine, the newly designed two-stage turbine will be adapted to the engine to give more efficiency and power to it. Firstly, the modelling and simulation of the engine were done in Gt-Power, to achieve the same power and torque curves presented in the MAN engine specification sheet. Once that was achieved, the second task was to design and optimise a radial and axial turbine, which will form part of a two-stage system, through Computational Fluid Dynamics (CFD) analysis. Necessary data were gathered from the engine’s output conditions, for the ability to design the new turbo system. Lastly, the new turbine data were entered into the new two-stage turbo GT-Power model, and a comparison of the results was made. The CFD analysis, executed in ANSYS, for the radial turbine gave an 83.4% efficiency at 85,000 rpm, and for the axial turbine, the efficiency achieved was 81.74% at 78,500 rpm.